(untitled) (diségno, 2022)
“An ark to save learning from the deluge,” as Francis Bacon described it in 1605 [1], such was the imaginative power of the cathedral of knowledge that here, since the 15th century and above all thanks to the expansion carried out by Thomas Bodley between 1598 and 1602 (Rogers 1991, tables 38, 43, 46), it finally found the right space in the first reading room in Oxford to be deliberately built for this function. The image represents the oldest of Oxford’s libraries and the historical core of the Bodleian Library, one of the oldest European public libraries and today an imposing cultural institution that houses millions of documents and 40 collections in 28 structures, which flourished after the decisive initiative of Thomas Bodley which, at the beginning of the seventeenth century, allowed its modern foundation and gave impetus to its constant growth by founding on the first small collection of manuscripts originally housed in Duke Humfrey’s Library, the important library complex of one of the most prestigious universities in the world. [read more]